Arbitration Court under Astana International Financial Centre - Myrzaliyeva, Zh.T. (Вестник Карагандинского университета, 2016)
The article deals with the problems of formation and current state of the Arbitration Court of the Republic of Kazakhstan and foreign countries and the implementation of the President of the Republic of Kazakhstan N.A. Nazarbayev’s National Plan «100 concrete steps» of Step 70 «the formation of Astana International Financial Center (AIFC) on the basis of ASTANA EXPO 2017 infrastructure, and giving it a special status».
Keywords: International commercial arbitrage; Arbitration Court; Astana International Financial Centre; National Plan 100 concrete steps